Multi-fractal modeling of curcumin release mechanism from polymeric nanomicelles. (31st December 2022) - (Tincu), Camelia E. Iurciuc; Popa, Marcel; Atanase, Leonard I.; Popa, Ovidiu; Ochiuz, Lacramioara; Postolache, Paraschiva; Ghizdovat, Vlad; Irimiciuc, Stefan A.; Agop, Maricel; Volovat, Constantin; Volovat, Simona
Abstract: The physicochemical properties of "smart" or stimuli-sensitive amphiphilic copolymers can be modeled as a function of their environment. In special, pH-sensitive copolymers have practical applications in the biomedical field as drug delivery systems. Interactions between the structural units of any polymer-drug system imply mutual constraints at various scale resolutions and the nonlinearity is accepted as one of the most fundamental properties. The release kinetics, as a function of pH, of a model active principle, i.e., Curcumin, from nanomicelles obtained from amphiphilic pH-sensitive poly(2-vinylpyridine)-b-poly(ethylene oxide) (P2VP-b-PEO) tailor-made diblock copolymers was firstly studied by using the Rietger-Peppas equation. The value of the exponential coefficient, n, is around 0.5, generally suggesting a diffusion process, slightly disturbed in some cases. Moreover, the evaluation of the polymer-drug system's nonstationary dynamics was caried out through harmonic mapping from the usual space to the hyperbolic one. The kinetic model we developed, based on fractal theory, fits very well with the experimental data obtained for the release of Curcumin from the amphiphilic copolymer micelles in which it was encapsulated. This model is a variant of the classical kinetic models based on the formal kinetics of the process.